Ethics in television commercials: an opinion survey of consumers on advertisements of Bangladeshi Companies - PARVEZ, M. H; EITEN, E. U. H (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The research is designed to explore consumers’ opinions about the renowned companies of Bangladesh in terms of maintaining an ethical standard in advertisements. Competition is very high among the top four business giants- Square Group, Akij Group, Bashundhara Group, and ACI Limited. This research digs the consumer base to find out whether they think that these companies maintain ethical principles, ensure customer’s rights, meet customers’ expectations and maintain quality as promised in TV commercials or not. Upon the findings, some recommendations are made for the companies to gain consumers’ trust by improving marketing strategies. RESUMEN La investigación está diseñada para explorar la opinión de los consumidores sobre las empresas de renombre de Bangladesh en términos de mantener el estándar ético en los anuncios. La competencia es muy alta entre los cuatro principales gigantes de negocios: Square Group, Akij Group, Bashundhara Group y ACI Limited. Esta investigación explora la base de consumidores para averiguar si creen que estas compañías garantizan los derechos de los clientes y mantienen la calidad como se prometió en los comerciales de televisión. Tras los hallazgos, se hacen algunas recomendaciones para que las empresas ganen la confianza de los consumidores al mejorar las estrategias de marketing.